Ichthyofauna in the peat swamp waters of East Kalimantan, Indonesia - A. S. Batubara; I. Zulfahmi; F. M. Nur; S. Maulizar; F. Maghfiriadi; B. Nafis; G. Wahyudewantoro; Z. A. Muchlisin; E. Prasetya; R. Mutia (The European Zoological Journal)
The exploration of ichthyofauna in the peat swamp waters of East Kalimantan is interesting to discover, not only has it never been reported, the relocation of Indonesia’s capital city to East Kalimantan is predicted to change the diversity of ichthyofauna in peat swamp waters. Therefore, species identification, distribution, conservation status and potency of fish are important to study and provide valuable references in formulating conservation policies for aquatic ecosystems. The observation parameters carried out in this study include the index of Shannon-Wiener diversity, Simpson dominance, and Sorensen similarity. In addition, the identified fish species are grouped based on their conservation status and potency (consumption and ornamental commodities). A total of 33 fish species were identified at four sampling stations belonging to 8 orders and 15 families with a total of 163 samples. Cyprinidae is the dominant family found with 14 species (33%). A total of 73% of fish collected have potential for fish consumption, 15% of species have potential as ornamental and consumption fish, and 12% of species have potential as ornamental fish. The conservation status (IUCN) of fish in the peat swamp waters of East Kalimantan is divided into five categories: Data Deficient (4 species: 13%), Least Concern (25 species: 78%), Near Threatened (1 species: 3%), Endangered (1 species: 3%), and Extinct (1 species: 3%). The species that was declared extinct was Chitala lopis in early 2021, but interestingly the species was rediscovered in this study in its natural habitat.